The psychology of rest in athletes: An empirical study and initial model. (September 2019) - Eccles, David W.; Kazmier, Alexander W.
Abstract: Objectives: To better understand the psychology of rest in athletes. Rest is central to an understanding of recovery, skill learning, and expertise development in athletes, yet extant conceptualizations of rest seldom extend beyond rest as inactivity. Design: A qualitative design was used to build an initial descriptive model of the psychology of rest in athletes. Method: 18 athletes and 4 staff members comprising a highly-ranked women's university field hockey squad were interviewed about meanings and experiences of rest. An inductive content analysis was undertaken to identify concepts within the interview data. Results: An initial descriptive model of the psychology of rest in athletes was proposed. Within this model, being well rested is considered to be a psychological state involving feeling fresh, and valuing, being motivating toward, and enjoying one's sport. Athletes become well rested by engaging in a resting process, which includes sleeping and wakeful resting. Wakeful resting involves key resting experiences including not thinking about one's sport. These experiences are obtained by engaging in specific activities (e.g., watching television) and within specific physical and social environments (e.g., being out of town). Obtaining resting experiences during in-season rest days is challenging due to limited time but more time is available to obtain these experiences during the off-season. Conclusion: The initial descriptive model proposed may offer analytical generalizability by having significance and utility within research with different sport contexts and populations that is concerned with recovery, skill learning, and expertise development. Highlights: An initial model of the psychology of rest in athletes is proposed. Athletes become well rested by engaging in a resting process. The resting process includes sleeping and wakeful resting. Wakeful resting involves resting experiences including not thinking about one's sport. Resting experiences are obtained by engaging in specific activities and environments.